Value-based decision making under uncertainty in hoarding and obsessive- compulsive disorders. (December 2017) - Pushkarskaya, Helen; Tolin, David; Ruderman, Lital; Henick, Daniel; Kelly, J. MacLaren; Pittenger, Christopher; Levy, Ifat
Abstract: Difficulties in decision making are a core impairment in a range of disease states. For instance, both obsessive- compulsive disorder (OCD) and hoarding disorder (HD) are associated with indecisiveness, inefficient planning, and enhanced uncertainty intolerance, even in contexts unrelated to their core symptomology. We examined decision-making patterns in 19 individuals with OCD, 19 individuals with HD, 19 individuals with comorbid OCD and HD, and 57 individuals from the general population, using a well-validated choice task grounded in behavioral economic theory. Our results suggest that difficulties in decision making in individuals with OCD (with or without comorbid HD) are linked to reduced fidelity of value-based decision making (i.e. increase in inconsistent choices). In contrast, we find that performance of individuals with HD on our laboratory task is largely intact. Overall, these results support our hypothesis that decision-making impairments in OCD and HD, which can appear quite similar clinically, have importantly different underpinnings. Systematic investigation of different aspects of decision making, under varying conditions, may shed new light on commonalities between and distinctions among clinical syndromes. Highlights: We examined differences in valuation and value-based choice under uncertainty in OCD and HD. OCD participants (with or without comorbid HD) demonstrated reduced fidelity of value-based decision making. HD participants chose similarly to controls. Fidelity of value-based decision making correlated positively with HD symptom severity. Decision-making impairments in OCD and HD, which can appear quite similar clinically, may have importantly different underpinnings.